Clinical connections - Tortora, Gerard J. (John Wiley & Sons, 2010)
Principles of Human Anatomy, the market-leading text through its many editions, successfully blends visual and textual elements to illuminate the complexities of human anatomy. A host of carefully crafted pedagogical aids support both the succinctly written narrative as well as the outstanding illustration program. Applications representing a variety of clinical perspectives provide readers with both relevance and motivation. The eleventh edition of the book continues to break new ground by offering readers a glimpse into the fascinating history of how we have come to know what we do. In addition, readers are given the opportunity to explore structure from diverse perspectives, and gain insights into the vital contributions that anatomical knowledge brings to the understanding of functions, diagnosis and treatment of disease